PENYULUHAN PENGARUH MAKANAN INSTAN TERHADAP POLA MAKAN DAN KESEHATAN REMAJA DI DESA MANUNGGAL - Yuana Delvika; Kamil Mustafa (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2017)
Busyness in various activities such as school and work often make teenagers number two basic needs, such as food. More business entities increasingly competing to produce instant food. Teenage thinking patterns change as well. "If there is an easy, why choose a difficult one?" In a day a teenager can consume some type of instant food from snacks until the staple food is replaced in the form of instant. As a result of excessive consumption of instant foods can make teenagers ignore a healthy diet. To provide knowledge to adolescents related to the dangers of consuming instant noodles, the lecturers of the Medan Medan Area (UMA) University are doing the service to the youth in Desa Manunggal. The purpose of this PpM activity is to provide knowledge to teenagers about the dangers of consuming instant foods and the importance of healthy lifestyle for the human body. The method used in the implementation of this activity is by doing counseling. This activity was attended by approximately 20 teenagers residing in Desa Manunggal. Outcome of this activity is the mindset and consumption patterns of teenagers are expected to change and can implement a healthy living culture.